2011
DOI: 10.1007/s12552-011-9051-5
|View full text |Cite
|
Sign up to set email alerts
|

Men and Their Father Figures: Exploring Racial and Ethnic Differences in Mental Health Outcomes

Abstract: Though gender, racial, and ethnic disparities in health in the United States are well documented, it is less clear how these factors intersect to produce patterns of mental health outcomes among men. This study examined the presence of father figures in the lives of African American, Caribbean black and non-Hispanic white American males until the age of 16; assessed the current socio-demographic factors of these men as adults; and explored whether these factors lead to variations in mental health outcomes. Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…We found six studies in social work journals that considered the influence of fathers and fatherhood in the mental health of Black men (Caldwell, Bell, Brooks, Ward, & Jennings, 2011; Fagan, 2009; Fagan & Stevenson, 2002; Huang & Warner, 2005; Sinkewicz & Lee, 2011; Watkins, Johnson-Lawrence, & Griffith, 2011). Overall, these studies suggested that not only do relationships with family members have implications for the presence of depressive symptoms, but the quality of these relationships is related to mental health outcomes for Black men.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found six studies in social work journals that considered the influence of fathers and fatherhood in the mental health of Black men (Caldwell, Bell, Brooks, Ward, & Jennings, 2011; Fagan, 2009; Fagan & Stevenson, 2002; Huang & Warner, 2005; Sinkewicz & Lee, 2011; Watkins, Johnson-Lawrence, & Griffith, 2011). Overall, these studies suggested that not only do relationships with family members have implications for the presence of depressive symptoms, but the quality of these relationships is related to mental health outcomes for Black men.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the Fagan and Stevenson study, the study by Watkins, Johnson-Lawrence, and Griffith (2011) also focused on the influence of father figures, as it included disaggregated racial and ethnic differences on mental health outcomes using a nationally representative sample of African American, Caribbean Black, and non-Hispanic White men. The authors reported that, compared to non-Hispanic White men, being raised by a grandfather placed African American and Caribbean Black men at higher risk for depressive symptoms and psychological distress under certain demographic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Although this study's focus was not a direct exploration of the experiences of oppression, due to diversity of the nonresident fathers as a group, it was important to us to consider the multiplicity of lived experiences among nonresident fathers. Multiple dimensions of identity may influence the experiences of nonresident parents, including gender, social class, and sexual orientation (Bunch et al 2002;Mobile fact sheet 2018;Trask and Hamon 2007;Watkins et al 2011). More research is needed to explore interplay identity in the context of parent-child relationships.…”
Section: Nonresident Fathersmentioning
confidence: 99%
“…Access to technology and expectations towards fathers may be a function of race, culture, gender, and socioeconomic status (Mobile fact sheet 2018; Trask and Hamon 2007;Watkins et al 2011). Moreover, due to the intersectionality of the experiences and oppressions (Bunch et al 2002), nonresident fathers of diverse backgrounds face layers of barriers when it comes to leisure participation and raising their children (Stodolska et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Oliffe () noted that the shifting social construction of masculinity, as shaped by age, social class, history, culture, and illness, influences specific illness events like prostate cancer. Watkins, Johnson‐Lawrence, and Griffith () examined how socialization experiences with grandfathers and father figures are related to mental health outcomes such as depression. The unfolding consequences of interparental violence is framed by life course epidemiology, as such violence leads to later‐life suicide attempts by witnessing children (Roustit et al, ).…”
Section: Multidisciplinary Focus On Change and Fatheringmentioning
confidence: 99%